Economic development and international projection of the Republic of Korea : towards a new stage of relations with Latin America and the Caribbean (SELA SantiagoCL, 1997)
Analyzes the Korean economy and its international participation, and looks at the Republic of Korea's economic relations with the Latin American and Caribbean region.
Located in the Office of the Secretary General